Solidarity Transformed : Labor Responses to Globalization and Crisis in Latin America - Anner, Mark Sebastian, 1963- (Book collections on Project MUSE., 2011)
Mark S. Anner spent ten years working with labor unions in Latin America and returned to conduct eighteen months of field research: he found himself in the middle of violent raids, was detained and interrogated in a Salvadoran basement prison cell, and survived a bombing in a union cafeteria. This experience as a participant observer informs and enlivens Solidarity Transformed, an illustrative, nuanced, and insightful account of how labor unions in Latin America are developing new strategies to defend the interests of the workers they represent in dynamic global and local contexts. Anner combines in-depth case studies of the auto and apparel industries in El Salvador, Honduras, Brazil, and Argentina with survey analysis. Altogether, he documents approximately seventy labor campaigns-both successful and failed-over a period of twenty years. Anner finds that four labor strategies have dominated labor campaigns in recent years: transnational activist campaigns; transnational labor networks; radical flank mechanisms; and microcorporatist worker-employer pacts. The choice of which strategy to pursue is shaped by the structure of global supply chains, access to the domestic political process, and labor identities. Anner's multifaceted approach is both rich in anecdote and supported by quantitative research. The result is a book in which labor activists find new and creative ways to support their members and protect their organizations in the midst of political change, global restructuring, and economic crises.